Complete Response to Chemotherapy in A Patient with Unresectable Extrahepatic Cholangiocarcinoma (Archives of Clinical and Medical Case Reports, 2019)
Introduction: Biliary tract cancer (BTC) is an uncommon tumor with bad prognosis. There is no curative treatment for patients with unresectable disease at diagnosis. There is a limited experience with second-line chemotherapy in advanced BTC since clinical trials are difficult to perform due to the rarity and heterogeneity of these tumors. Recent molecular studies have increased our understanding of the pathogenetic mechanism that underly the development of cholangiocarcinoma. These will help us to determine the significance of molecular alterations that occur in this disease and will direct the development of targeted therapy. Case Report: This case report describes a radiological complete response after three cycles of second-line chemotherapy with the combination of capecitabine and oxaliplatin in a patient with unresectable extrahepatic cholangiocarcinoma, after treatment with the combination of gemcitabine and cisplatin as first-line chemotherapy. Conclusion: Our case suggests that selected patients may demonstrate very good responses to chemotherapy. There is an urgent need to identify different molecular subtypes that could direct management of these patients.